ダイ19ジ ナンキョク チイキ カンソクタイ チョウセキ カンソク ホウコク 1978ネン1ガツ～12ガツ - 鈴木, 元之; スズキ, モトユキ; 蔵野, 隆夫; クラノ, タカオ; Suzuki, Motoyuki; Kurano, Takao (1982)
P(論文) 昭和基地で実施されている潮汐観測のうち, 1978年1月から12月までの観測成果およびその解析結果について報告する. This report presents the results of tidal observation and its analysis. The data were observed at Syowa Station, Antarctica, (69°00′S, 39°35′E) from January to December 1978. departmental bulletin paper